Autoantibodies to box A of high mobility group box 1 in systemic lupus erythematosus. (27th March 2017) - Schaper, F.; de Leeuw, K.; Horst, G.; Maas, F.; Bootsma, H.; Heeringa, P.; Limburg, P. C.; Westra, J.
Summary: Autoantibodies to nuclear structures are a hallmark of systemic lupus erythematosus (SLE), including autoantibodies to nuclear protein high mobility group box 1 (HMGB1). HMGB1 consists of three separate domains: box A, box B and an acidic tail. Recombinant box A acts as a competitive antagonist for HMGB1 and might be an interesting treatment option in SLE. However, antibodies to box A might interfere. Therefore, levels of anti‐box A were examined in SLE patients in association with disease activity and clinical parameters. Serum anti‐box A was measured in 86 SLE patients and 44 age‐ and sex‐matched healthy controls (HC). Serum samples of 28 patients with primary Sjögren's syndrome and 32 patients with rheumatoid arthritis were included as disease controls. Anti‐HMGB1 and anti‐box B levels were also measured by enzyme‐linked immunosorbent assay during quiescent disease [SLE Disease Activity Index (SLEDAI) ≤ 4, n = 47] and active disease (SLEDAI ≥ 5, n = 39). Anti‐box A levels in active SLE patients were higher compared to quiescent patients, and were increased significantly compared to HC and disease controls. Anti‐box A levels correlated positively with SLEDAI and anti‐dsDNA levels and negatively with complement C3 levels. Increased levels of anti‐box A antibodies were present in the majority of patients with nephritic (73%) and non‐nephritic exacerbations (71%). Antibodies to the box A domain of HMGB1 might be an interesting new biomarker, as these had a high specificity for SLE and were associated with disease activity. Longitudinal studies should be performed to evaluate whether these antibodies perform better in predicting an exacerbation, especially non‐nephritic exacerbations. Abstract : Auto‐antibodies to nuclear structures are a hallmark of systemic lupus erythematosus (SLE), including auto‐antibodies to nuclear protein High Mobility Group Box‐1 (HMGB1). Antibodies to the Box A domain of HMGB1 might be an interesting new biomarker, as these had a high specificity for SLE and were associated with disease activity. Longitudinal studies should be performed to evaluate whether these antibodies perform better in predicting an exacerbation, especially non‐nephritic exacerbations.